(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of treatment adherence among outpatients with type 2 diabetes at General Hospital of Agricultural in 2025; to analyze several factors associated with treatment adherence among the study population. Subjects and methods: A cross-sectional descriptive study was conducted on 300 outpatients with type 2 diabetes from January to June 2025. A structured questionnaire was used to assess overall treatment adherence, defined as adherence to all four components: diet, physical activity, medication use, and blood glucose monitoring with follow-up visits. Data were analyzed using SPSS software, employing descriptive statistics (percentages) and Chi-square tests, with a significance level set at p < 0.05. Results and conclusions: The study revealed that only 33.3% of patients with type 2 diabetes adhered fully to all four components of the treatment regimen. Among these, adherence to blood glucose monitoring and follow-up visits was relatively low (50.3%). Several factors were statistically associated with non-adherence, including lower educational level, being employed, not living with a spouse, inadequate knowledge about the disease, and the presence of diabetes-related complications.